Comparison of single‐ and multiple‐dose cefazolin as prophylaxis for transurethral enucleation of prostate: A multicenter, prospective, randomized controlled trial by the Japanese Research Group for Urinary Tract Infection. (21st January 2020) - Togo, Yoshikazu; Fukui, Koji; Ueda, Yasuo; Kanamaru, Sojun; Shimizu, Yosuke; Wada, Koichiro; Sadahira, Takuya; Yamada, Yusuke; Matsumoto, Masahiro; Hamasuna, Ryoichi; Ishikawa, Kiyohito; Takai, Manabu; et al.
Abstract : Objectives: To compare the optimal administration period of antimicrobial prophylaxis in patients undergoing transurethral enucleation of the prostate for benign prostatic hyperplasia. Methods: We carried out a randomized controlled trial to compare the differences in incidence of perioperative genitourinary tract infection between single and multiple (3 days) administrations of cefazolin for transurethral enucleation of the prostate in benign prostatic hyperplasia patients without pyuria or bacteriuria between January 2015 and December 2018. Results: This multicenter randomized controlled trial included 203 patients who underwent a transurethral enucleation of the prostate procedure. All received antimicrobial prophylaxis, and were randomized into those who received single‐dose ( n  = 101) or multiple‐dose ( n  = 102) therapy. The rate of genitourinary tract infection after transurethral enucleation of the prostate for all patients was 1.5%, whereas that in the single‐dose group was 1.0% and in the multiple‐dose group was 2.0%, which were not significantly different ( P  = 1.00). Conclusions: A single dose of antimicrobial prophylaxis as a prophylactic antibacterial drug is sufficient for patients undergoing transurethral enucleation of the prostate who do not have presurgical pyuria or bacteriuria.